Risk factors for complicated appendicitis among pediatric population - Murthy, Pramod Sreekanta; Panda, Amrit Preetam (Indian Journal of Child Health, 2018)
Context: Appendicitis is the most common surgical emergency in children. In children, it is difficult to diagnose appendicitis due to atypical presentation. Various risk factors have been mentioned in literature leading to complicated appendicitis. Aims: Our study was to determine the risk factors for complicated appendicitis in children. Methodology: The children who underwent appendectomy with a clinical diagnosis of acute appendicitis from 2015 to 2018 were studied retrospectively at Kempegowda Institute of Medical Sciences and Hospital, Bengaluru. The pre-operative, operative, and post-operative data were analyzed. Statistical analysis was performed and variables analyzed were age, sex, location of patient, duration of symptoms, total leukocyte count, and fecolith. Statistical Analysis Used: Categorical variables were analyzed by applying Chi-square test and continuous variables were analyzed by applying independent t-test. Results: A total of 220 children presented with appendicitis during the study period, of which 60 children had complicated appendicitis. Mean age of presentation was 10.38±2.84 years. On statistical analysis, patients having pain of duration >48 h (p=0.017), patients with leukocyte count >15000/mm3 (p